2015
DOI: 10.1016/j.mod.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Socs36E limits STAT signaling via Cullin2 and a SOCS-box independent mechanism in the Drosophila egg chamber

Abstract: The Suppressor of Cytokine Signaling (SOCS) proteins are critical, highly conserved feedback inhibitors of signal transduction cascades. The family of SOCS proteins is divided into two groups: ancestral and vertebrate-specific SOCS proteins. Vertebrate-specific SOCS proteins have been heavily studied as a result of their strong mutant phenotypes. However, the ancestral clade remains less studied, a potential result of genetic redundancies in mammals. Use of the genetically tractable organism Drosophila melanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…In Drosophila melanogaster , loss of function of CUL2 resulted in defects at the larval neuromuscular junction and aberrations in the development of female germ line [ 72 ]. Cul2 was also required to limit the number of motile cells in egg chambers [ 73 ] and for germline enclosure in testes [ 74 ]. Among several CRL2 complexes that were associated with germline development, CRL2 LRR-1 complex was a critical one.…”
Section: Main Textmentioning
confidence: 99%
“…In Drosophila melanogaster , loss of function of CUL2 resulted in defects at the larval neuromuscular junction and aberrations in the development of female germ line [ 72 ]. Cul2 was also required to limit the number of motile cells in egg chambers [ 73 ] and for germline enclosure in testes [ 74 ]. Among several CRL2 complexes that were associated with germline development, CRL2 LRR-1 complex was a critical one.…”
Section: Main Textmentioning
confidence: 99%
“…We tested our models to confirm if they reproduced certain behaviors identified in various experiments. It has been shown that if STAT activity is blocked by stage 9 of cell migration, the level of APT protein drops by about half (Starz-Gaiano et al, 2008 , 2009 ; Yoon et al, 2011 ; Monahan and Starz-Gaiano, 2015 ). It is also known that increasing the initial condition of APT should decrease the level of STAT protein and activity (Starz-Gaiano et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…One was the decision to ignore the c 2 equation, which allows APT to act as a buffer on STAT. Since the action of APT on STAT is known to function by preventing activation through miRNAs (Yoon et al, 2011 ) as well as limiting active protein present (Monahan and Starz-Gaiano, 2015 , 2016 ), this assumption might oversimplify the larger system. Additionally, the quasi-steady state assumptions made in reducing STAT dynamics may also oversimplify the model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations